Search engine marketing - Ditlefsen, Lisa (Henry Stewart Talks, 2008)
Why search engine marketing, What is SEO (search engine optimization) and PPC (pay per click) advertising, Organic and paid results, How search engines work, The importance in ranking highly in the search engines result pages, Principles of search engine optimization, Keyword and competitor research, Trend analysis tools, Targeting and mapping, Content optimization, Optimizing the title tag, Meta description tag, Unethical search engine optimization, Link building and google PageRank, Web analytics
Archived at 2022/03/17